A Hahn-Ramsey scheme for dynamical decoupling of single solid-state qubits - Sadzak, Nikola; Carmele, Alexander; Widmann, Claudia; Nebel, Christoph; Knorr, Andreas; Benson, Oliver (Frontiers in Photonics, 2022)
Spin systems in solid state materials are promising qubit candidates for quantum information in particular as quantum memories or for quantum sensing. A major prerequisite here is the coherence of spin phase oscillations. In this work, we show a control sequence which, by applying RF pulses of variable detuning, allows to increase the visibility of spin phase oscillations. We experimentally demonstrate the scheme on single NV centers in diamond and analytically describe how the NV electron spin phase oscillations behave in the presence of classical noise models. We hereby introduce detuning as the enabling factor that modulates the filter function of the sequence, in order to achieve a visibility of the Ramsey fringes comparable to or longer than the Hahn-echo $T_2$ time and an improved sensitivity to DC magnetic fields in various experimental settings.